2019
DOI: 10.1155/2019/7693459
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Management Software for Factory Production of Modular Buildings

Abstract: After the first modular construction project in Korea in 2003, the scope and demand for modular systems have gradually increased. However, modular producers in Korea utilize spreadsheets to manage the process, manpower, and materials required for modular construction. This is inadequate compared to other countries that are more advanced in modular construction such as Japan and the United Kingdom. The management system in Korea decreases the effectiveness of modular construction in reducing construction time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Arashpour et al [50] and Nam et al [51] developed a system for the management of the factory production stage. Arashpour et al [50] indicated that inaccurate production tracking in the factory production stage results in schedule delays, and increased construction costs; they developed a system to predict a short-term shortage in production, and the likelihood of achieving long-term target production utilizing statistical techniques.…”
Section: Osc Project Management Systemmentioning
confidence: 99%
“…Arashpour et al [50] and Nam et al [51] developed a system for the management of the factory production stage. Arashpour et al [50] indicated that inaccurate production tracking in the factory production stage results in schedule delays, and increased construction costs; they developed a system to predict a short-term shortage in production, and the likelihood of achieving long-term target production utilizing statistical techniques.…”
Section: Osc Project Management Systemmentioning
confidence: 99%
“…For example, if we assume the simulated process for the given constraint factors as purple from the below diagram (Figure 3), three (3) objective functions exist. As an area function, the difference between the total utilized factory area should be minimized as shown in Equation (2). In other words, we can assume that the area is used as much as possible under the given constraint factors.…”
Section: Category Prefabricated Lightweight Steel Prefabricated Lightmentioning
confidence: 99%
“…Modular construction involves the production of construction components (e.g., structures, materials, various types of equipment) that are built off-site, and modules are assembled with minimal effort on-site [1][2][3]. In modular construction-a type of industrialized construction-factory production is very important, as it is closely related to the project's duration, quality, and sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, the need to improve productivity has paved the way for advanced and emerging techniques and technologies, each with their own characteristics. In recent years, advanced techniques, such as prefabrication, automation, and IT-based techniques, have drastically altered the construction industry, changing its focus from traditional practice to modern enterprise [45].…”
Section: Emerging Advanced Techniques For Construction Projectsmentioning
confidence: 99%